2009
DOI: 10.1002/psp.575
|View full text |Cite
|
Sign up to set email alerts
|

From ‘fish out of water’ to ‘fitting in’: the challenge of re‐placing home in a mobile world

Abstract: Recent academic arguments in transnational and mobility studies have emphasised fl uid and fl exible understandings of concepts such as place and home. This paper, however, will argue that the desire to fi x home with particular meaning by attaching it to place is still apparent even for highly mobile migrants, and seeks to explore why this is the case. Using data from qualitative research with a group of highly mobile Australian transnational professionals working in Asia, the paper elaborates on social, mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…In her research on highly mobile individuals, Butcher (2010) argues there is still a 'need' for home, even if this home becomes multi-sited. She suggests that being a 'global citizen' does not negate the need to 'feel the ground beneath their feet' and as such to have somewhere (or many places) that can be called home (ibid, p. 34).…”
Section: Destabilising Binaries Of 'Home' and 'Away'mentioning
confidence: 99%
“…In her research on highly mobile individuals, Butcher (2010) argues there is still a 'need' for home, even if this home becomes multi-sited. She suggests that being a 'global citizen' does not negate the need to 'feel the ground beneath their feet' and as such to have somewhere (or many places) that can be called home (ibid, p. 34).…”
Section: Destabilising Binaries Of 'Home' and 'Away'mentioning
confidence: 99%
“…This aspect has been emphasised in studies examining the meanings that migrants attach to home at different geographical scales, highlighting the de‐territorialisation of belonging and attachments (Appadurai, ). At the same time, the desire to fix home with particular meanings by attaching it to an immediate locale is still apparent even for highly mobile transnational migrants (Butcher, ). Ralph and Staeheli () make the point that there has been a tendency to overemphasise the shifting and mobile meanings of home, while underplaying migrants' struggles in, and attachments to, their current home.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that, while interpersonal and symbolic ties with the host country did not lead to the development of transnational practices or the circulation of remittances, they did have a highly important symbolic and emotional value. This is because, first, these ties meet the respondents' strong need and desire to retain a connection with a place and community of which they had once felt a part and from which their return has now separated them (Butcher 2010;Coutin 2000;Drothbom 2011;Pedersen 2003;Weiss 2005). Second, their experiences of transnational belonging are important because they may function as meaningful symbolic capital, as proof of their migration experience and of their ties with Belgium.…”
Section: The Return-transnationalism Nexus: the Boundaries And Importmentioning
confidence: 99%